Assessment of the relationship between organ donation attitudes and religious beliefs among postgraduate students - Apak, Umit; Akbulut, Sami; Kucukakcali, Zeynep; Saritas, Hasan (Frontiers in Public Health, 2025)
BackgroundOrgan donation is a critical public health issue, and understanding the factors influencing individuals' knowledge, attitudes, and awareness is essential. To address this, we conducted a descriptive and analytical study among postgraduate students, aiming to evaluate the relationship between their knowledge, attitudes, and awareness of organ donation and their religious beliefs.MethodsA survey-based cross-sectional study was conducted among about 500 postgraduate students at Inonu University Health Sciences Institute. A demographic information form, an organ donation knowledge form, and the validated Turkish version of the Organ Donation Attitude Scale (ODAS) were used. Data were collected online via Google Forms, except for 10 students who filled out paper forms due to email issues. Independent variables included age, marital status, education programs, alcohol and cigarette use, and awareness of organ donation, while dependent variables were ODAS total and subdimension scores.ResultsA total of 324 postgraduate students completed the survey. Despite 96.5% recognizing the necessity of organ donation, only 16.9% reported having registered as donors. Religious beliefs were important for 92.5% of postgraduate students, influenced major decisions for 62.2%, and 65.8% believed organ donation was compatible with Islam. The ODAS total scores showed no significant differences based on gender (p = 0.073), marital status (p = 0.483), education program (p = 0.051), or the influence of religious beliefs on life decisions (p = 0.135). Doctoral postgraduate students were more aware of the fatwa on organ donation (p = 0.010). Postgraduate students who had not donated an organ were significantly more likely to believe that brain death is reversible (p < 0.001), to disapprove of organ donation from a Muslim to a non-Muslim (p = 0.004), and to consider organ donation incompatible with Islam (p < 0.001). The Cronbach's alpha value of the ODAS scale was 0.841, indicating good internal consistency.ConclusionAlthough religious beliefs influenced major life decisions for most postgraduate students, they did not significantly alter attitudes toward organ donation, as measured by ODAS scores. Misconceptions about brain death and religious permissibility persist, highlighting the need for targeted educational programs, especially considering that postgraduate students, as future health professionals, can play a crucial role in promoting organ donation awareness.